2010
DOI: 10.1016/j.jenvman.2010.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian farmers ceasing certified organic production: Characteristics and reasons

Abstract: a b s t r a c tThis article examines the characteristics of and reasons for Norwegian farmers' ceasing or planning to cease certified organic production. We gathered cross-sectional survey data in late 2007 from organic farmers deregistering between January 2004 and September 2007 (n ¼ 220), and similar data from a random sample of farmers with certified organic management in 2006 (n ¼ 407). Of the respondents deregistering by November 2007, 17% had quit farming altogether, 61% now farmed conventionally, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 19 publications
3
48
0
2
Order By: Relevance
“…Some studies show that labour requirement on organic versus conventional farms does not reflect a decision rule for adopting or not adopting organic farming [3,37,38]. External factors, in particular labour availability, are likely to become increasingly relevant and should be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show that labour requirement on organic versus conventional farms does not reflect a decision rule for adopting or not adopting organic farming [3,37,38]. External factors, in particular labour availability, are likely to become increasingly relevant and should be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, some authors contend that labour seems not to be crucial in farmers' decision to expand or reduce farm size [38], whether organic or not, and that the higher labour requirement on organic farming is of intermediate importance as a reason for opting out of organic farming [3]. Type of labour (hired versus family labour) was found to be related with the adoption of organic farming by Larsen [39], who suggested that the probability to adopt organic methods increases with the share of hired labour.…”
Section: Labour Use In Farmers' Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite large fluctuations in the organic sector with many farmers adopting and abandoning organic production each year, the organic sector in the EU has increased over the past 10 years, mainly due to policy support and market demand for organic products 4 . Given the commitment of many European governments to increase the size of their organic sectors and considering the large withdrawal rate from organic agriculture, it seems important to implement measures to prevent organic farmers from ceasing production rather than focusing on recruiting new farmers 5 . However, in order to decrease the number of farmers abandoning organic farming, more information about organic, former organic and conventional farmers is required.…”
Section: Introductionmentioning
confidence: 99%
“…Similar challenges have been found to hinder organic farming even in some other European countries like Norway (Flaten et al, 2010). The increment in costs was due to the need to utilize more organic fertilizers and also carry out frequent weeding in order to get fruits of better intrinsic quality as demanded by the local and export markets.…”
Section: Resultsmentioning
confidence: 84%